Joint Operating Agreements in Oil and Gas Industry: The Consequence of Sole Risk and Non Consent Clauses to Joint Operation - Marshall, Junaidu Bello (Journal of Asian Business Strategy, 2017)
The paper examines the Joint Operating Agreement (JOA) with a view to ascertaining the purposes of sole risk and non-consent clauses in JOA and their incompatibility or otherwise with the joint objectives of the agreement. The nature of Oil and Gas Industry is such that involved very huge costs and project risks are enormous, especially where the project requires new infrastructure for successful undertaking. Even the few Oil companies that are capable of conducting such projects are usually not willing to take the huge risks alone. For such reasons therefore, Oil Companies in other to mitigate its various levels of costs and risks make joint applications for licence acreage. The purpose of this application is to enable two or more companies to share costs, risks and benefits in agreed proportions in the licence acreage regime they obtained together. The method commonly used by Oil Companies in achieving these joint objectives is through JOA. The paper adopts doctrinal methodology where relevant primary and secondary data were utilised. The paper observed that parties to JOA used sole risk and non-consent clauses in order allow dissenting parties an opportunity to benefit from their omission without terminating the main agreement of the parties. The paper recommends that parties shall from the onset recognise the consequences of JOA and couched the sole risk and non-consent clauses in a flexible manner that will not jeopardise the objectives of JOA. That is to say, the clauses should not be used in a manner that will defeat the major aim of the parties’ relationship.